The correlation between TAM,MVD, VEGF andMMP-9 expressions among various histological progression, histological grading and staging of breast cancer - Irianiwati, Harijadi Surendra Prabawa, Yulius Hermanto Angelina Septiana, Brian Arditya M (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Breast cancer may progress from an atypical lesion. Angiogenesis has an important role in thegrowth, invasion and metastasis of breast cancer, which can be reflected through the microvasculardensity (MVD). Tumor associated macrophages (TAMs) are stromal cells that can produce proangiogenicfactor such as vascular endothelial growth factor (VEGF), and induce matrixmetalloproteinase-9 (MMP-9) for degrading extracellular matrix and basement membrane.Angiogenesis in breast cancer progression and its relationship with histological grading as wellas its staging need to be defined and thus, cancer therapy and prognosis can be determinedmore accurately. The aim of this study was to investigate the correlation between TAM, MVD,VEGF and MMP-9 expressions among fibrocystic lesion, atypical lesion and breast cancer, andits correlation with histological grading and staging of breast cancer. Using a cross-sectionalstudy, a total of 50 paraffin embedded tissues of fibrocystic lesion, atypical lesion and breastcancer were chosen in this study. Those specimens were stained immunohistochemically withmonoclonal antibody (MoAb) anti CD68, von Willebrand factor (vWF), VEGF and MMP-9. Theexpressions of VEGF and MMP-9 were counted from the mean numbers of positive tumor cells.TAMs were counted from numbers of macrophages which expressed CD-68. MVDs were countedfrom numbers of microvessels whose endothelial cells expressed vWF, using the AverageMicrovessels Count ( AMC) method. The correlation of both markers and different type of breastlesions were analyzed by using Pearson correlation. There were statistically significant correlationsbetween TAM (r=0.760; p=0.000), MVD (r=0.659; p=0.000), and MMP-9 (r=0.518; p=0.000),among several breast lesions and histological grade of breast cancer. The highest of theirexpressions was found in the poor grade of cancers. There were statistically significant correlationsbetween TAM (r=0.581; p=0.000), VEGF (r=0.443; p=0.001) and MVD (r=0.566; p=0.000)among fibrocystic, atypical lesion and stage II - III of breast cancer. VEGF expression was notsignificantly correlated with several histological grade of breast cancer and the highest of itsexpression was only found in atypical lesion. This study has suggested that TAM, MVD, VEGFand MMP-9 expressions might play an important role in the histological progression, histologicalgrading and staging of breast cancer. The highest expression of VEGF in atypical breast lesionsupported the fact that angiogenic switch already started in the early stage and grade of breastcancer.